Predictive diagnostics of lymph nodes metastatic lesion in patients with gastric adenocarcinoma - O. I. Kit; D. S. Kutilin; M. Z. Tatimov; A. A. Maslov; E. M. Frantsiyants; D. I. Vodolazhsky (Медицинский вестник Юга России, 2018)
Objective: lymph node metastases occur in 90% of cases in patients with gastric adenocarcinoma, and survival is less than 15% in the late stages of disease. Therefore, the purpose of the study was to screening markers for predicting the likelihood of metastases developing in gastric adenocarcinoma. Materials and methods: for the study 47 patients with diagnosis of gastric adenocarcinoma were used (with the localized tumor form T3-4N0M0 (n = 18) and the locally distributed form T3-4N1-3M0 (n = 29)). The copy number variation of 16 genes (APC, AURKA, CCND1, C-MYC, GKN1, HER2, IRX1, MDM2, MET, NFKB, OCT1, P53, PIK3CA, POU5F1B, S6K2 and HV2) was determined by RT-PCR. Immunohistochemical studies were performed on sections of paraffin blocks using monoclonal antibodies to p53, Bcl-2, Ki-67 and Her2. Results: the loss of duplicity of HV2 locus was most frequent CNV in samples of stomach adenocarcinoma, but CNV significant change in the T3-4N0M0 group relative to T3-4N1-3M0 was not detected. A significant increase of CNV in the T3-4N1-3M0 group relative to T3-4N0M0 was found in 2 of 16 loci - NFKB and HER2 in 1.75 and 1.90 times (p<0.0005), respectively. Th e value of p53 expression in the tumor cells nuclei in the group without metastases was lower by 52% compared to the expression in the metastatic group (p<0.05). Low proliferative activity prevailed in the group without metastases in contrast to the group with metastases, in which Her2 overexpression was also observed in 43% of cases in contrast to 20% of cases in the group without metastases. Conclusions: it was showed that the relative copies number of NFKB1 and HER2 in combination with the immunohistochemical parameters of Ki67 and HER2 in gastric tumors can be a prognostic marker of metastasis, and algorithm for predicting metastases development in gastric adenocarcinoma is formed on basis of this.